Reduction of ammonia emissions by applying a urease inhibitor in naturally ventilated dairy barns. (April 2021) - Bobrowski, Anna B.; Willink, Diliara; Janke, David; Amon, Thomas; Hagenkamp-Korth, Frauke; Hasler, Mario; Hartung, Eberhard
Abstract : Ammonia emissions damage the environment and have negative consequences for human and animal health. In the German livestock sector, most ammonia emissions come from naturally ventilated dairy barns. To reduce emissions, Germany has signed the EU Directive 2016/2284 to achieve a stepwise decrease in the ammonia emissions ceiling. The aim of this study was to investigate the seasonal mitigation effect of a urease inhibitor under practical conditions and provide information relating to two theoretical application scenarios in order to estimate an annual application scenario. The experimental design was conducted according to the requirements of the Verification of Environmental Technologies for Agricultural Production test protocol using the CO2 balance method to obtain the emissions. In a manual process, the inhibitor was applied to the floor surfaces of two dairy farms. The application took place once a day over three days during summer, winter and the transition period (spring/autumn). The ready-to-use liquid formulation of 1% inhibitor K dissolved in pyrrolidone was mixed with water resulting in 2.5 mg m −2 application rate of inhibitor and 50 ml m −2 water. The ammonia emissions on Farm A and Farm B were reduced by 40% and 53% in summer, 65% and 68% in winter and 64% and 54% in transition period, respectively. Thus, an annual reduction of 58% on Farm A and 57% on Farm B was observed. In a theoretical scenario where no inhibitor was applied during winter, up to 41% of the annual reduction was observed. Highlights: Ammonia emissions were measured at two naturally ventilated farms. First calculation of reduction effect by a urease inhibitor under field conditions. Indications for the inhibitor application under field conditions could be provided. The estimated reduction potential over the seasons ranged between 40% and 68%. The application technique can be retrofitted in existing and newbuild housing.